Referral writing: Consensus building on a tool for writing structured referrals - Azhar, Faryal; Ahmed Khan, Rehan; Tausief Fatima; Raheela Yasmin; Mehboob, Usman (Journal of the Pakistan Medical Association, 2022)
Competency in referral writing skill is needed by doctors for which they are never trained. Although there is a lot of work done about improvement of consultation letters still priority is not given. There must be a course for teaching and learning medical referral writing skills to students along with the assessment. Currently there is such tool to assess the way communication letter are written. An 18-point assessment scale has been developed through Delphi technique to increase the quality of referral letters. The objective of the present study was to design a structured Performa for writing referrals, validated by 7 participants using Delphi. Results were finalised after the acceptance of structured referral by selected participants through Delphi. The response rate was 70%. The validity and interrater reliability were calculated using SPSS25. The Cronbach’s alpha was 0.7 and Kappa was 0.3. Both were statistically significant. The designed Performa for writing referrals, with its inter-rater reliability calculated, is best for writing effective and structured referrals. The study further recommending training junior doctors in making proper referrals. MeSH Words: Referral and consultation, improving quality and referral, Checklists and referrals and consultation.